Redesigning Islamic Education Funding in the West: The Singapore Model and its Relevance for Islamic Schools - Mohammed Ghufran Ahmed; Syed Musa Alhabshi; Habeebullah Zakariyah (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025